2011
DOI: 10.1111/j.1750-3841.2011.02122.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Acetate and Potassium Lactate Enhance the Microbiological and Physical Properties of Marinated Catfish Fillets

Abstract: Sodium or potassium salts such as lactate and acetate can be used to inhibit the growth of spoilage bacteria and food-borne pathogens, and thereby prolong the shelf-life of refrigerated seafood. However, minimal information is available regarding the combined effects of potassium salts (acetate and lactate) with an agglomerated phosphate blend on the quality and safety of refrigerated catfish fillets. The objective of this study was to determine the microbiological and quality characteristics of marinated catf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…No differences existed (p > 0.05) among treatments with respect to shear force and total energy ( Table 2). The force required to shear the smoked catfish fillet samples ranged from 23.9 to 29.3 N/g which was higher than those (17 N/g) for non-smoked catfish fillets that were marinated and baked (Kin et al, 2011). This demonstrated that baked catfish fillets were more tender than smoked or non-smoked fillets that were processed in the smokehouse in the current study.…”
Section: Physicochemical Analysiscontrasting
confidence: 67%
See 1 more Smart Citation
“…No differences existed (p > 0.05) among treatments with respect to shear force and total energy ( Table 2). The force required to shear the smoked catfish fillet samples ranged from 23.9 to 29.3 N/g which was higher than those (17 N/g) for non-smoked catfish fillets that were marinated and baked (Kin et al, 2011). This demonstrated that baked catfish fillets were more tender than smoked or non-smoked fillets that were processed in the smokehouse in the current study.…”
Section: Physicochemical Analysiscontrasting
confidence: 67%
“…The pH and tenderness of smoked catfish fillets (4 fillets per treatment for each replication) were evaluated using methods described by Kin et al (2011). Surface color of smoked catfish fillets (4 fillets per treatment for each replication) was measured by a method described by Jackson et al (2009).…”
Section: Physicochemical Measurementsmentioning
confidence: 99%
“…Hardness‐1, which is a measure of force to compress the fish between the ball probe and plate during the first compression, was significantly greater for the fresh‐frozen catfish than the IQF catfish (Table ). The tenderization that occurred during the injection of water solution, likely contributed to less force required for compression (Kin et al., ). The force during the second compression (hardness‐2) was greater in the fresh‐frozen catfish, also.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, potassium lactate (PL) and sodium diacetate (SDA) have been approved by the U.S. Food and Drug Administration (FDA) for use to improve the safety and the quality of RTE meat products (FDA ). Many researchers have also used lactate, diacetate, or a combination of them in smoked salmon (Yoon and others ), catfish fillet (Kin and others ), turkey (Velugoti and others ; Shafit and Williams ), beef (Ponrajan and others ), sliced ham (Mellefont and Ross ), and pork (Velugoti and others ; Min and others ). In addition, lactate, diacetate, or a combination of them were tested to inhibit the germination and the outgrowth of C. perfringens spores in meat products (Velugoti and others ; b; Jackson and others ).…”
Section: Introductionmentioning
confidence: 99%